COVID-19 vaccination in mastocytosis: recommendations of the European Competence Network on Mastocytosis (ECNM) and American Initiative in Mast Cell Diseases (AIM) - Bonadonna, Patrizia; Brockow, Knut; Niedoszytko, Marek; Elberink, Hanneke Oude; Akin, Cem; Nedoszytko, Boguslaw; Butterfield, Joseph H.; Alvarez-Twose, Ivan; Sotlar, Karl; Schwaab, Juliana; Jawhar, Mohamad; Castells, Mariana; et al. (The journal of allergy and clinical immunology. In practice, 2021)
Mastocytosis is a neoplasm characterized by an accumulation of mast cells in various organs and increased risk for severe anaphylaxis in patients with concomitant allergies. Coronavirus disease 2019 (COVID-19) is a pandemic that is associated with a relatively high rate of severe lung disease and mortality. The mortality is particularly high in those with certain comorbidities and increases with age. Recently, several companies have developed an effective vaccination against COVID-19. Although the reported frequency of severe side effects is low, there is an emerging discussion about the safety of COVID-19 vaccination in patients with severe allergies and mastocytosis. However, even in these patients, severe adverse reactions are rare. We therefore recommend the broad use of COVID-19 vaccination in patients with mastocytosis on a global basis. The only well-established exception is a known or suspected allergy against a constituent of the vaccine. Safety measures, including premedication and postvaccination observation, should be considered in all patients with mastocytosis, depending on the individual personal risk and overall situation in each case. The current article provides a summary of published data, observations, and expert opinion that form the basis of these recommendations.
Gesehen am 24.08.2021